A influência da arte de Beatriz Milhazes como representação no vestuário - Gomes, Jane Mary Silvestre (2015)
This paper aims to make a relationship between art and fashion, with the inclusion of information of contemporary art works of artist Beatriz Milhazes, in women's fashion apparel products for the conservative and evangelical public. It is noticed that this audience is faced with difficulty in finding fashion products that bring design, comfort, quality and style the public, which needs to dress according to the doctrine her religion.